Goal Orientations among Yarmouk University Students and their Relationship with Self- Regulated Learning - Ahmad Y. Banimufarrej; Shafiq F. Alawneh (Sultan Qaboos University, 2014)
This study aimed at exploring the relationship of goal orientations with self-regulated learning among Yarmouk University students in light of faculty and gender. The sample of the study consisted of 684 students. Two scales were used: a goal orientations scale, and aself-regulated learning scale. The results showed statisticallysignificant differences in the means of participants' scores on the goal orientation scales due to the student gender in mastery goals, and performance-avoidance goals; females scored higher on these subscales than males. No significant gender difference was found in performance-approach goals. The results also showed significant differences in the means scores on the self-regulated learning scale due to gender; females once again scored higher than males on all skills, except for the planning and goal specification skill. No significant difference, however, was found in self-regulated learning due tostudent faculty or the interaction between faculty and gender.